2018
DOI: 10.3892/etm.2018.7121
|View full text |Cite
|
Sign up to set email alerts
|

Ropivacaine at different concentrations on intrapartum fever, IL‑6 and TNF‑α in parturient with epidural labor analgesia

Abstract: Effects of ropivacaine at different concentrations on intrapartum fever, interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in parturient with epidural labor analgesia were compared to provide reference for the rational selection of anesthetics in clinic. Medical records of 198 cases of primi-paras admitted to the Obstetrics and Gynecology Department, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, from January 2017 to January 2018 were analyzed retrospectively and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(20 reference statements)
0
15
0
Order By: Relevance
“…We also speculate that it may be related to the low concentration of local anesthetics we use and the intermittent pulse infusion of the analgesia pump. This view has been supported in previous studies, many of which found that duration of epidural analgesia is associated with intrapartum fever in most cases in which high concentrations of local anesthetics were used, or in which the epidural analgesia pattern was continuous [ 17 19 ].…”
Section: Discussionmentioning
confidence: 55%
“…We also speculate that it may be related to the low concentration of local anesthetics we use and the intermittent pulse infusion of the analgesia pump. This view has been supported in previous studies, many of which found that duration of epidural analgesia is associated with intrapartum fever in most cases in which high concentrations of local anesthetics were used, or in which the epidural analgesia pattern was continuous [ 17 19 ].…”
Section: Discussionmentioning
confidence: 55%
“…Riley et al found that women with ERMF had higher levels of proinflammatory cytokines (IL-6 and IL-8) even before receiving epidural analgesia, and the subsequent prolonged use of epidural bupivacaine increased the baseline cytokine levels gradually [ 14 ]. Zhou et al found that the IL-6 and tumor necrosis factor (TNF)-α levels of their 0.075% ropivacaine group were significantly lower than those of their 0.1% ropivacaine group [ 15 ]. The use of 0.075% ropivacaine caused less inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dexmedetomidine inhibited tumor necrosis factor-a and interleukin-6 expression to alleviate inflammation by suppression of c-Jun N-terminal kinases [19]. A recent document reported that lower concentrations of ropivacaine reduced the rate of intrapartum fever during labor analgesia [20].…”
Section: Discussionmentioning
confidence: 99%